ANALYSIS OF LEARNING AND LITERATURES THROUGH WHO HAS FOLLOWED EDUCATION - Dewi, A. Erni Ratna (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
The purpose of this research is to analyze the influence of independent learning and literacy through artificial intelligence on the quality of education. Type of research with quantitative descriptive approach with samples based on purposive sampling of 236 state high school teachers from the region of the district of Tamalanrea. Data collection techniques in this research through questionnaires, library studies, and observations. Data analysis techniques using Structural Equation Modeling (SEM) software WarpPLS 7.0. Data analysis results, show that independent learning and literacy variables have a significant influence on artificial intelligence.